Rheumatoid and psoriatic knee synovitis: clinical, grey scale, and power Doppler ultrasound assessment of the response to etanercept. Issue 6 (26th November 2004) - Fiocco, U; Ferro, F; Vezzù, M; Cozzi, L; Checchetto, C; Sfriso, P; Botsios, C; Ciprian, L; Armellin, G; Nardacchione, R; Piccoli, A; Todesco, S; et al.
Abstract : Objective: To determine the effect of tumour necrosis factor α (TNFα) blockade with etanercept in refractory knee joint synovitis (KJS) in rheumatoid and psoriatic arthritis, by local and systemic disease activity assessment and combined grey scale and power Doppler ultrasonographic monitoring. Methods: 27 knees affected by rheumatoid KJS (n = 12) and psoriatic KJS (n = 8) were assessed before receiving treatment and at 3 and 12 months' follow up. Time dependent clinical changes in disease activity were monitored by C reactive protein, erythrocyte sedimentation rate (ESR), global health status (GHS), and Ritchie (RAI) and knee joint articular (KJAI) indices; synovial changes were monitored by ultrasonographic and power Doppler indices for grey scale synovial thickening and for distinct intrasynovial vessel power Doppler flow configurations (fluid/synovium interface (F/SI-PD) and pannus/cartilage interface (P/CI-PD)). Interobserver and intraobserver variability of grey scale and power Doppler ultrasonographic was evaluated. Response to treatment was assessed by analysis of variance for repeated measures on clinical and ultrasonographic variables. Results: Rapid (3 months) reduction in F/SI-PD flow (p<0.001), parallel to reductions of C reactive protein (p<0.05), ESR (p<0.001), KJAI (p<0.002), RAI, and GHS (p<0.001), was sustained at 12 months when it was accompanied by reduction in both synovial thickening and P/CI-PD flow (p<0.001). No differences (ANOVA) were noted at baseline or at 12 months in clinical and ultrasonographic variables between either the rheumatoid or the psoriatic KJS groups. Conclusion: Grey scale and power Doppler ultrasonography are reliable measures of long term change in rheumatoid and psoriatic KJS disease activity in response to anti-TNFα treatment with etanercept.